Educação do campo pela decolonialidade de gênero: vivências das egressas do curso de pedagogia PRONERA/UFPB (2015-2019) - Araújo, Aline Praxedes de (2023)
This doctoral thesis, linked to the Line of Research on Popular Education within the Graduate Program in Education at the Federal University of Paraíba (PPGE/UFPB for its Portuguese acronym), focuses on the biographical narratives of women graduates from the undergraduate program in Pedagogy (2015-2019) offered by the National Agrarian Reform Education Program (PRONERA for its Portuguese acronym) at UFPB, specifically at its Education Center. This work‟s general objective is to identify how gender decoloniality in the formative processes of the PRONERA/UFPB Pedagogy program (2015-2019) manifests in the lives of its women graduates by analyzing their biographical narratives. Our research is developed by pursuing the following specific objectives: to present the collaborators‟ view of Rural Education; to try to understand the collaborators‟ biographical narratives based on social and cultural contexts; to note the different meanings that higher education assumes throughout their life stories. The theoretical framework is in line with Popular Education, the decolonial gender debate, and Oral History, while a dialogue is established with the Rural Education legislation. This work also dialogues with authors such as Brandão (1994), Paludo (2013), Alheit (2011), Caldart (2012), Freire (2014), Lugones (2014), Meihy (2020), Mignolo (2008), Tardin (2012), Walsh (2005), among others. The methodological procedures included bibliographic and documentary research, as well as semi-structured interviews with the nine women graduates of the aforementioned program. The experiences and knowledge provided in the program were observed to have strengthened in our collaborators their peasant identity, which allowed for changing their conceptions about the rural area and themselves. Thus, this thesis has helped evaluate the contributions of a Rural Education public policy, as it has highlighted its historical and social importance for all the peoples provided with Rural Education at university level in order to ensure the right of access to and continuation of education.